INTERNALISASI KARAKTER RELIGIUS DALAM EKSTRAKURIKULER PRAMUKA DI MADRASAH TSANAWIYAH DARUSSALAM SENGKUBANG - Saputra, Nanang; Suriadi , Suriadi; Susilawati , Susilawati (ILJ: Islamic Learning Journal, 2024)
Extracurricular activities are a place to develop the potential of students through various activities, both those directly related and those not directly related to the curriculum. Extracurricular activities can bridge the problems of education that occur in schools and education in families as well as the challenges of globalisation because they act as a perfecting education from the cognitive level to the affective and psychomotor aspects. As well as extracurricular activities at MTs darussalam sengkubang which can shape the religious character of students through habituation and cultivation in extracurricular scout activities. This research uses a qualitative approach, while this type of research is phenomenology. The results showed that the implementation of extracurricular scout activities at MTs Darussalam Sengkubang began with the planning stage of long-term, medium and short-term work programmes, then the implementation stage of the planned programme with a well-calculated time determination. In the implementation of extracurricular scout activities at MTs Darussalam Sengkubang, it strongly emphasises the character development of students or scout members. Scout extracurricular activities can shape the religious character of students at MTs Darussalam Sengkubang because of the provision of religious guidance to students, involving students in scouting activities and guidance from administrators and coaches able to internalise the religious character of students.